If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -4) + -6 = 12 + -48 Reorder the terms: 3(-4 + x) + -6 = 12 + -48 (-4 * 3 + x * 3) + -6 = 12 + -48 (-12 + 3x) + -6 = 12 + -48 Reorder the terms: -12 + -6 + 3x = 12 + -48 Combine like terms: -12 + -6 = -18 -18 + 3x = 12 + -48 Combine like terms: 12 + -48 = -36 -18 + 3x = -36 Solving -18 + 3x = -36 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + 3x = -36 + 18 Combine like terms: -18 + 18 = 0 0 + 3x = -36 + 18 3x = -36 + 18 Combine like terms: -36 + 18 = -18 3x = -18 Divide each side by '3'. x = -6 Simplifying x = -6
| 2y-1/3=4y | | 12-6k=36 | | -16=0.1x-0.5x | | x^2+100=125 | | X=arcsiney | | 2x+5x=88 | | m+2+m-5=15 | | lg(x-1)=0 | | 4x^3-4x^2+x=o | | 22-9x=-5(6x+3)-5(-4-4x) | | 13+X=37 | | 3x+5y=8fory | | 5[4-(-3)(2)]= | | -8*[7+(-15)*(3)]= | | 5y-4-7=2+3 | | z=10*x*y+5*x*y | | 5y-4y-7=2+3 | | 4-[4x+(-5x+6)+5]= | | -12-10=6y+14 | | 11x-2=4x-30 | | f(x)=2x^2-3x^2-1 | | 6xy*3= | | a=2d | | 2b-2=b+1 | | 2a+3=a-5 | | 4x+13=-20+7x | | 2x+11=-19+4x | | 7x+9=-21+x | | 5-2x=8-3x | | 2x-5=8-3x | | 37=-3+5(u+6) | | 0=x^4-2x^2 |